Arthroscopically Assisted Eaton–Littler Trapeziometacarpal Ligamentoplasty - Moungondo, Fabian G.P.; Gkotsi, Antonia; Camus, Emmanuel; Van Overstraeten, Luc; Schuind, Frédéric A. (Journal of Wrist Surgery, 2021)
Background Eaton–Littler ligamentoplasty has proven its efficacy in the treatment of trapeziometacarpal (TMC) instability.Description of Technique In this article, we describe the arthroscopically assisted Eaton–Littler ligamentoplasty through two clinical cases.Patients and Methods Arthroscopy is used to accurately place the metacarpal bone tunnel and pass the slip of flexor carpi radialis tendon in the latter. This procedure avoids soft-tissue dissection and could improve the outcome of this well-known surgery.Results The two clinical cases showed good short-term outcome with a decrease of pain and good function.Conclusions Arthroscopy to assist Eaton–Littler TMC ligamentoplasty is technically feasible, allowing a less invasive surgery. A larger prospective controlled study with a longer term outcome is mandatory to assess the real advantages of this modified procedure.
Keywords: arthroscopy; Eaton–Littler ligamentoplasty; instability; osteo-arthrosis; trapeziometacarpal joint